Theology and history in the methodology of Herman Bavinck: revelation, confession, and Christian consciousness - Clausing, Cameron D. (Oxford studies in historical theology, 2024)
"This book examines the theological methodology of Dutch theologian, Herman Bavinck (1854-1921). The focus of the book is on the influence of the German historicist movement on his theological method and uses Bavinck's doctrine of the Trinity as a way to test the argument that while not embracing all of the relativising implications of the movement, the role of history as a force that both shapes the present and allows for development into the future has a demonstrable influence on his theological methodology. To make this argument the book considers Bavinck's larger nineteenth century context. It traces the development of both history and theology being understood as sciences in the university and how this required a reimagining of both disciplines. It could be said that the theology is thoroughly historicised in the nineteenth century. The book then considers the three principia of Bavinck's theological methodology: Revelation, Confession, and Christian Consciousness, demonstrating how Bavinck both appropriates and adapts historicist assumptions"--